Effects of antibiotics on callus induction in sorghum and subsequent growth of callus - ZHANG Ming-zhou; CUI Hai-rui; SHU Qing-yao; XIA Yin-wu (浙江大学学报. 农业与生命科学版)
Growth inhibition of Agrobacterium by 3 different antibiotics was demonstrated. Carbenicillin and cefotaxime gave better results than ampicillin in inhibiting Agrobacterium growth. Cefotaxime was significantly more toxic than carbenicillin in induction of callus in sorghum. Carbenicillin of concentration below 500 mg/L in MS medium showed positive effects on sorghum callus growth. The regeneration rate of shoots from sorghum callus, however, was decreased with increase of carbenicillin level from 50 mg/L to 1000 mg/L in MS medium. The ideal concentration of carbenicillin was 250 mg/L when used in genetic transformation of sorghum mediated by Agrobacterium. Sorghum callus was more sensitive to hygromycin than to kanamycin. Considering the rate of browning (dying), the responses to kanamycin and hygromycin were different among different sorghum genotypes. With hygromycin as the selection marker, the optimal selecting pressure was 50-75 mg/L.